Influence of Ni content on structural, magnetocaloric and electrical properties in manganite La0.6Ba0.2Sr0.2Mn1−xNixO3 (0 ≤ x ≤ 0.1) type perovskites. Issue 7 (1st February 2022) - Dhahri, Ahmed; Laifi, J.; Gouadria, Soumaya; Elhadi, M.; Dhahri, E.; Hlil, E. K.
Abstract : We present a detailed study on the physical properties of La0.6 Ba0.2 Sr0.2 Mn1− x Ni x O3 samples ( x = 0.00, 0.05 and 0.1). Abstract : We present a detailed study on the physical properties of La0.6 Ba0.2 Sr0.2 Mn1− x Ni x O3 samples ( x = 0.00, 0.05 and 0.1). The ceramics were fabricated using the sol–gel route. Structural refinement, employing the Rietveld method, disclosed a rhombohedral R 3̄ c phase. The magnetization vs. temperature plots show a paramagnetic–ferromagnetic (PM–FM) transition phase at the T C (Curie temperature), which decreases from 354 K to 301 K. From the Arrott diagrams M 2 vs. μ 0 H / M, we can conclude the phase transition is of the second order. Based on measurements of the isothermal magnetization around T C, the magnetocaloric effects (MCEs) have been calculated. The entropy maximum change (−Δ S M ) values are 7.40 J kg −1 K −1, 5.6 J kg −1 K −1 and 4.48 J kg −1 K −1, whereas the relative cooling power (RCP) values are 232 J kg −1, 230 J kg −1 and 156 J kg −1 for x = 0.00, 0.05 and 0.10, respectively, under an external field ( μ 0 H ) of 5 T. Through these results, the La0.6 Ba0.2 Sr0.2 Mn1− x Ni x O3 (0 ≤ x ≤ 0.1) samples can be suggested for use in magnetic refrigeration technology above room temperature. The electrical resistivity ( ρ ) vs. temperature plots exhibit a transition from metallic behavior to semiconductor behavior in the vicinity of T M–SC . The adiabatic small polaron hopping (ASPH) model is applied in the PM-semiconducting part ( T > T MS ). Throughout the temperature range, ρ is adjusted by the percolation model. This model is based on the phase segregation of FM-metal clusters and PM-insulating regions.